Health education of the youth via peer education - Milošević Georgiev, Andrijana; Krajnović, Dušanka; Brzaković, Jelena; Stević, Ivana; Marinković, Valentina (Archives of Pharmacy, 2022)
Peer education (PE) is a more effective strategy for improving the health of adolescents than traditional methods (for example, teacher training). Along the improvement of knowledge, beliefs, attitudes and behaviours between students are also improved with various medical problems in mind. We analysed the positive and negative sides of PE from the perspective of students, as well as how many would be interested in peer-to-peer education. A cross-sectional study has been conducted in November and December of 2020 on a sample of students from the Faculty of Pharmacy, University of Belgrade (N = 145), using a purpose-built questionnaire. Dominant were females (83.4%). As the most significant positive side, 44.8% of respondents state that they are better acquainted with the issues and the way of thinking of peer educators. As the main shortcoming, the largest number of respondents (97.8%) state insufficient experience and training of peer educators. Students would like to be educators (51.3%), mostly on the topic of disease prevention, health promotion and healthy lifestyles (20.3%). The results show that students have positive attitudes towards peer education, which need to be further researched, especially because of its importance in adolescence.